1993
DOI: 10.1073/pnas.90.9.3983
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from in vitro replication that O6-methylguanine can adopt multiple conformations.

Abstract: The effect of O6-methylguanine (m6G) on replication, in a partiafly double-stranded defined 25-base oligonucleotide, has been studied under nonlimiting conditions of unmodified dNTPs and over an extended time period, using the Klenow fragment of Escherichia coli DNA polymerase I. The sequence surrounding m6G has flanking cytosines (C-m6G-C), and the initial steady-state kinetics have been reported. When the primer was annealed so that the first base to be replicated was m'G, replication was virtually complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Interestingly, computational modeling with yeast RNAPII showed that bypass of O 6 mG can only occur when the lesion adopts an anti -conformation with the methyl group in the proximal orientation and that accommodation of the misincorporated uracil involves specific hydrogen bonding 64 . As for 8-oxoG, this specific scheme of pairing during transcription is similar to the one used to explain thymine misincorporation during replication 65 .…”
Section: The Mechanism Of Transcriptional Mutagenesismentioning
confidence: 79%
“…Interestingly, computational modeling with yeast RNAPII showed that bypass of O 6 mG can only occur when the lesion adopts an anti -conformation with the methyl group in the proximal orientation and that accommodation of the misincorporated uracil involves specific hydrogen bonding 64 . As for 8-oxoG, this specific scheme of pairing during transcription is similar to the one used to explain thymine misincorporation during replication 65 .…”
Section: The Mechanism Of Transcriptional Mutagenesismentioning
confidence: 79%
“…In this respect pol ␤ is similar to KF, T4 and T5 polymerases which also preferentially insert dTMP (17)(18)(19). On the other hand, pol ␤ has an opposing 2-fold (13-fold from a running start) preference for extension from dC-m 6 dG rather than dT-m 6 dG.…”
Section: Table I Kinetic Parameters Of Running Start Nucleotide Insermentioning
confidence: 99%
“…In vitro studies (17)(18)(19), as well as in vivo mutagenesis assays (20,21) have shown that m 6 dG preferentially base pairs with dTMP instead of dCMP, thus giving rise to G to A transition mutations. The importance of these lesions has been repeatedly demonstrated.…”
mentioning
confidence: 99%
“…Nonenzymatic methylation by exogenous and endogenous methylating agents (e.g., (S)-adenosylmethionine and N-methyl-N-nitrosourea) [3,4], however, gives rise to a wide variety of genotoxic DNA lesions, including O6-methylguanine and N7-methylguanine [5,6]. O6-methylguanine represents a minor yet highly mutagenic lesion due to its ability to disrupt Watson–Crick base pairing during replication [7,8,9,10]. N7-methyl-2-deoxyguanosine (m7dG) is the predominant alkylative DNA lesion found in cells [11,12].…”
Section: Introductionmentioning
confidence: 99%